Online Travel Retail Site Usage And Generational Differences When Using Sites To Plan A Leisure Vacation - Salazar, John; Hritz, Nancy; Moorman, Catherine; Brunson, Kelli; Abraham, Anton (European Scientific Journal, ESJ, 2016)
The growth of online travel agencies has modified how consumers explore possible vacation choices by allowing greater access to the travel and tourism supply chain. This growth also empowers potential travelers to be more discerning when purchasing travel products and services by giving them the opportunity to align their preferences (i.e., price, value, amenity, etc.) with the multiple product offerings available to them via online travel retail sites. This research explores a visitor’s frequency of using online travel sites when planning a leisure vacation and if similarities exist in how frequently these sites are used in the planning process. It also examines if generational differences exist in utilizing these sites. The factor analysis showed that 10 types of online travel sites can be categorized into two factors, and the ANOVA indicated that site frequency usage differs by generation. These findings can be beneficial to both managers of online travel sites and direct suppliers of travel products.